Reduced Graphene Oxide-Poly (Ionic Liquid) Composite Films of High Mechanical Performance - Chang, Jian; Zhou, Xianjing; Zhao, Qiang; Cao, Wei; Zhang, Miao; Yuan, Jiayin (Frontiers in Materials, 2021)
Graphene and its derivatives are a classic group of two dimensional (2D) building blocks possessing excellent mechanical and/or electrical properties in favor of preparing flexible electronic devices. Natural materials, e.g. nacre, provide inspiration and an exciting guideline for assembling 2D nanosheets into functional nanocomposites. In this context, despite recent advance, methods to assemble graphene-derived nanosheets into nanocomposites with the integrated enhancement of mechanical properties and electrical conductivity are eagerly pursued. Here, a rational design has been proposed and demonstrated, which utilizes synergistic supramolecular interactions between a polymeric additive and reduced graphene oxide nanosheets to fabricate exceptional integrated strong and tough nanocomposite films with high electrical conductivity. Such materials can be applied in areas of, e.g. aerospace, artificial muscle, tissue engineering, and flexible electronics.